High-quality Ge and Sn Thin Films Deposited on Si Substrate by Magnetron Sputtering. (2017) - Qian, Li; Ni, Peinan; Xu, Zhengji; Tong, Jinchao; Fan, Weijun; Zhang, Dao Hua
Abstract: Gex Sn1-x is one of the most promising materials in optoelectronics for its direct band-gap nature. In this paper, we report high-quality Ge and Sn thin films deposited on Si (001) substrates by magnetron sputtering. We found that the growth power and chamber pressure affect the quality of the Ge and Sn thin films significantly but in different ways. By optimizing the deposition conditions, high quality Ge and Sn films are achieved. A clear peak of Ge (004) phase in the x-ray diffraction (XRD) pattern which indicates a high-quality Ge lattice formed is observed, and post-treatment like rapid thermal annealing does not significantly affect the quality of the thin films.